2018
DOI: 10.1111/apm.12852
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of doublecortin‐like kinase 1 expression in locally advanced rectal cancer treated with preoperative chemoradiotherapy

Abstract: Preoperative chemoradiotherapy (CRT) is a standard therapy for locally advanced rectal cancer; however, the response varies depending on cases. Therefore, CRT-response predictors need to be elucidated. Cancer stem cells (CSCs), comprising a small part of tumors, are associated with tumor progression and recurrence due to their self-renewal and proliferation abilities. Doublecortin-like kinase 1 (DCLK1) is one of the several putative CSC markers; however, the clinical impact of its expression in rectal cancer h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In addition, it includes a doublecortin domain which modulates a C-terminal serine-threonine protein kinase domain [4]. DCLK1 has been reported to be closely related to the occurrence and metastasis of rectal cancer [5]. Moreover, the prognosis of GC patients was worse with the increase in DCLK1 expression in tissues of patients [6], and DCLK1 can activate Notch signalling pathway [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it includes a doublecortin domain which modulates a C-terminal serine-threonine protein kinase domain [4]. DCLK1 has been reported to be closely related to the occurrence and metastasis of rectal cancer [5]. Moreover, the prognosis of GC patients was worse with the increase in DCLK1 expression in tissues of patients [6], and DCLK1 can activate Notch signalling pathway [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many research teams have associated DCLK1, analyzed in different tumors, with metastasis, tumor invasion, and prognosis. ( 18,38,40,41 ) Moreover, Nakanishi et al ( 14 ) demonstrated that the ablation of DCLK1 in tumor stem cells resulted in regression of intestinal polyps within mouse models. DCLK1 has been proposed as a marker of quiescent stem cells in both the pancreas and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Whorton et al(16) and Sureban et al(39) demonstrated in their studies that in the malignant condition the concentration of DCLK1 in the patient serum, in oesophageal adenocarcinoma and HCC respectively, was higher than pre-cancer conditions (Barrett's oesophagus and liver cirrhosis, respectively). Many research teams have associated DCLK1, analysed in different tumours, with metastasis, tumour invasion, and prognosis (18,38,40,41). Moreover, Nakanishi et al(14) demonstrated that the ablation of DCLK1 in tumour stem cells resulted in regression of intestinal polyps within mouse models.…”
Section: Accepted Articlementioning
confidence: 99%
“…Resistance to radiation therapy is associated with alterations within the tumour and in the surrounding microenvironment, such as DNA repair, growth signalling pathways, inflammation, angiogenesis and oxygen tension [8]. Thus, in order to avoid unnecessary treatments, costs and adverse events, a major effort has been directed either toward the development of pharmacological agents able to enhance response to radiation, or to the identification of predictors of the response to CRT [9]. It is now widely accepted that tumour maintenance is due to cancer stem cells (CSCs), a minority subset of tumour cells with stemness properties, able to undergo self-renewal and multi-lineage differentiation, sustain malignant growth and mediate CRT response [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…CSCs have been demonstrated to display a higher capacity of DNA damage repair and a robust capability to initiate local and metastatic spread. CSC elimination can reduce the incidence of recurrence, metastasis and chemoresistant phenotype, which in turn effectively enhances sensitivity to therapy in advanced CRC patients [9,13,14]. Cellular resistance to CRT remains the primary barrier to overcome in order to achieve treatment success and improve RC prognosis; an increasing body of evidence from both experimental and clinical studies indicates that the likelihood of achieving local tumour control by CRT depends on the complete eradication of CSC populations [15].…”
Section: Introductionmentioning
confidence: 99%